A review of forest carbon cycle models on spatiotemporal scales. (10th March 2022) - Zhao, Junfang; Liu, Dongsheng; Zhu, Yujie; Peng, Huiwen; Xie, Hongfei
Abstract: The carbon cycle of forest ecosystems plays an important role in cutting down global environmental pressure, reducing greenhouse effects, and assimilating carbon dioxide. Model simulation has developed rapidly and become an irreplaceable method in researching carbon cycle mechanisms and estimating carbon fluxes of forest ecosystems. So far, little research has systematically reviewed the progresses in forest carbon cycle models. A review of forest carbon cycle models on spatiotemporal scales will be timely and valuable. In this paper, the forest carbon cycle models on spatiotemporal scales were reviewed, and the advantages and disadvantages of forest carbon cycle models at different spatiotemporal scales were compared. The existing problems of forest carbon cycle models were analysed. Proposals on the prospects of forest carbon cycle models in the future were presented. This review can provide new ideas and a comprehensive understanding on the assessment method development of current forest carbon cycle.